2016
DOI: 10.1007/s00702-016-1620-8
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta polymorphisms and cognitive performance in women: associations and modifications by genetic and environmental influences

Abstract: Genetic and environmental risk factors contribute to the pathogenesis of Alzheimer's dementia. Besides known genetic risk factors like the apolipoprotein (APO) Eε4 allele, single nuclear polymorphisms (SNPs) of the estrogen receptors (ESRs) are candidate genetic risk factors, while air pollution represents an environmental risk factor for dementia. Effects of these risk factors and their interaction were investigated in the SALIA cohort of 834 non-demented elderly women. Cognitive function was assessed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
7
1
Order By: Relevance
“…The study of Fernández-Martínez et al [13] showed increased risk of mild dementia and AD in the simultaneous presence of the APOE ε4 allele and polymorphic variants of both XbaI and PvuII polymorphisms within the ESR1 gene. Opposite to our study, Fehsel et al [11] found no relation of ESR1 polymorphisms and cognition, but minor variants of ESR2 polymorphisms had a significant impact on executive function in women carrying the APOE ε4 allele. In addition, the authors observed that air pollution increased the risk of cognitive decline in women.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The study of Fernández-Martínez et al [13] showed increased risk of mild dementia and AD in the simultaneous presence of the APOE ε4 allele and polymorphic variants of both XbaI and PvuII polymorphisms within the ESR1 gene. Opposite to our study, Fehsel et al [11] found no relation of ESR1 polymorphisms and cognition, but minor variants of ESR2 polymorphisms had a significant impact on executive function in women carrying the APOE ε4 allele. In addition, the authors observed that air pollution increased the risk of cognitive decline in women.…”
Section: Discussioncontrasting
confidence: 99%
“…It is also suggested that both ESR1 polymorphisms may have an impact on cognitive functioning [9,10]. However, there are also contrary results in the topic [11].…”
Section: Introductionmentioning
confidence: 99%
“…[23] For example, the Estrogen Receptor-2 (ESR2) allele is implicated in gene-environment interactions. [24]…”
Section: Air Pollution and Cognitive Dysfunctionmentioning
confidence: 99%
“…Although a number of trials examined interaction effects of MHT with APOE genotype, none examined interactions with polymorphisms in other genes as part of the main study, and to our knowledge, no comprehensive examination of the relationship between MHT and genotypes of estrogen biosynthesis, metabolism, and transporter genes has been conducted. Polymorphisms of ERβ have been associated with increased risk of AD 122,123 and cognitive performance, 124 while polymorphisms in both estrogen biosynthesis genes, including COMT, CYP17, and CYP19A1, [125][126][127] and metabolism genes, including CYP11A1, 122 have been associated with AD. Genotypes of SULT1A1, an estrogen metabolism gene, and SLCO1B1, an estrogen transporter, affect estrogen levels and subtype balance; 120,128 other gene polymorphisms also likely influence MHT effects.…”
Section: Challenges and New Frontiersmentioning
confidence: 99%